Synthesis, Supramolecular Structural Investigations of Co(II) and Cu(II) Azido Complexes with Pyridine-Type Ligands - Mezna Saleh Altowyan; Jörg H. Albering; Assem Barakat; Saied M. Soliman; Morsy A. M. Abu-Youssef (Crystals, 2023)
Two new Co(II) and Cu(II) azido complexes with 4-picoline (4-Pic) and pyridine-2-carboxaldoxime (HAld) were synthesized by self-assembly of the organic ligand and the M(II) nitrate in the presence of azide as a co-ligand. Their structures were determined to be [Co(4-Pic)4(H2O)(N3)]NO3*H2O*4-Pic (1) and [Cu(HAld)(Ald)(N3)] (2) using X-ray single crystal diffraction. In complex 1, the coordination geometry is a slightly distorted octahedron with a water molecule and azide ion located trans to one another. On the other hand, complex 2 has a distorted square pyramid CuN5 coordination sphere with N-atoms of the organic ligand as a basal plane and azide ion as apical. All types of intermolecular contacts and their contributions in the molecular packing were analyzed using Hirshfeld analysis. The intermolecular contacts, H…H (53.9%), O…H (14.1%), N…H (11.0%) and H…C (18.8%) in 1, and H…H (27.4%), N…H (27.7%), O…H (14.7%) and H…C (13.6%) in 2 have the largest contributions. Of all the contacts, the O…H, N…H and C…C interactions in 2 and the O…H, N…H and H…C in 1 are apparently shorter than the van der Waals radii sum of the interacting atoms. Atoms in molecules (AIM) topological parameters explained the lower symmetry of the coordinated azide in 1 than 2.